Strengthening Regional Fiscal Resilience through Local Own Source Revenue Optimization for Mitigating Payment Delays and Budget Efficiency Pressures - Arbi Winarko (Golden Ratio of Data in Summary, 2026)
This study examines how local own-source revenue optimization strengthens regional fiscal resilience by mitigating payment delays and budget efficiency pressures in Dumai City. Using a descriptive case study with a mixed-methods approach, the research analyzes official budget realization reports, regional financial statements, delayed payment records, and policy alternatives through the USG and Dunn evaluation methods. The findings show that low realization of local own-source revenue, which reached only 60.03% of the 2024 target, weakened cash availability, triggered IDR 346.88 billion in delayed payments, and reduced fiscal space in the following budget year. The main causes include weak data-based revenue management, unrealistic fiscal planning, limited supervision, and poor interagency coordination. The study recommends integrating and digitalizing local revenue management through real-time monitoring, early warning systems, and data-based forecasting. This policy can improve budget credibility, reduce fiscal risks, and strengthen sustainable regional fiscal governance within Indonesian decentralized local public financial management contexts.